2007
DOI: 10.1128/aem.00110-07
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of UVC Light Sensitivity of Vaccinia Virus

Abstract: Interest in airborne smallpox transmission has been renewed because of concerns regarding the potential use of smallpox virus as a biothreat agent. Air disinfection via upper-room 254-nm germicidal UV (UVC) light in public buildings may reduce the impact of primary agent releases, prevent secondary airborne transmission, and be effective prior to the time when public health authorities are aware of a smallpox outbreak. We characterized the susceptibility of vaccinia virus aerosols, as a surrogate for smallpox,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 26 publications
(22 reference statements)
6
68
0
Order By: Relevance
“…Similarly, Sidwell et al (1966) reported VACV was less stable in high humidity environments (78% RH). In line with these findings, McDevitt et al (2007) showed the survival of aerosolized vaccinia in the presence of UVC is significantly influenced by RH.…”
Section: Vacvsupporting
confidence: 76%
See 3 more Smart Citations
“…Similarly, Sidwell et al (1966) reported VACV was less stable in high humidity environments (78% RH). In line with these findings, McDevitt et al (2007) showed the survival of aerosolized vaccinia in the presence of UVC is significantly influenced by RH.…”
Section: Vacvsupporting
confidence: 76%
“…In an earlier study, Jensen (1964) reported VACV is highly susceptible to UVC with >99% viral inactivation with short exposure times. McDevitt et al (2007) found similar results, demonstrating VACV susceptibility to UVC. In 1965, Rauth investigated the UVC sensitivity in the range 225-302 nm for 12 medically important viruses including VACV, and postulated the susceptibility of vaccinia to UV inactivation is the result of its relatively large size and adsorption cross-section compared with those other viruses (Rauth, 1965).…”
Section: 1supporting
confidence: 75%
See 2 more Smart Citations
“…For instance, the viability of agents contained in an aerosol particle can be diminished by deleterious environmental stressors, such as ultraviolet radiation. 46 However, pathogens residing at the core of a larger (> 10 mm) infectious aerosol may experience a protective effect from environmental stressors, depending on the consistency and composition of the carrier fluid (eg, mucus). 36 Particle size does nonetheless determine the initial deposition pattern within the respiratory tract and, ultimately, the ability of the deposited BSAT to initiate disease.…”
mentioning
confidence: 99%